Prevalence of adsorbed A antigen onto donor‐derived group O red cells in children following stem cell transplantation: A single‐centre evaluation. Issue 2 (9th December 2022) - Cripps, Kelly; Mullanfiroze, Khushnuma; Hill, Annette; Moss, Rachel; Kricke, Susanne
Abstract: Background and Objectives: A group AB D‐positive child presented 1 year after haematopoietic stem cell transplant (HSCT) from a group O D‐negative donor as group A D‐negative. Engraftment remained at 100% in white cell lineages. The reason for the unusual result was explored, and the scarcely reported phenomenon of adsorption of secreted antigen was considered. This study also investigated the prevalence of secreted antigen adsorbed onto donor‐derived group O red blood cells (RBCs) in children after HSCT and defined a process for laboratory management. Materials and Methods: Retrospective data analysis of HSCTs carried out over 19 months at Great Ormond Street Hospital was conducted to identify cases of adsorbed A antigen after HSCT. Investigation of RBC reactions with different clones of anti‐A and in vitro experiments was performed to recreate adsorption. Results: Nineteen A to O HSCTs were conducted over 19 months, of which six (31%) displayed weak A antigen on RBCs despite full myeloid engraftment. Negative reactions with anti‐A were obtained when run on an alternative clone. Laboratory protocols for the future management of these cases have been developed. Conclusion: Passive adsorption of secreted antigen is responsible for these results and is more widespread than previously reported, as a third of A to O HSCTs at our centre demonstrated this phenomenon. A process has been implemented into the laboratory to manage this cohort, ensuring component groups compatible with both donor and recipient are given, and the shared care centres are aware of these requirements.